Moment Tensor Solutions for Earthquakes in the Southern Korean Peninsula Using Three-Dimensional Seismic Waveform Simulations - Song, Jung-Hun; Kim, Seongryong; Rhie, Junkee; Park, Donghee (Frontiers in Earth Science, 2022)
Precise estimates of earthquake source properties are crucial for understanding earthquake processes and assessing seismic hazards. Seismic waveforms can be affected not only by individual event properties, but from the Earth’s interior heterogeneity. Therefore, for accurate constraints on earthquake source parameters, the effects of three-dimensional (3D) velocity heterogeneity on seismic wave propagation need evaluation. In this study, regional moment tensor solutions for earthquakes around the southern Korean Peninsula were constrained based on the spectral-element moment tensor inversion method using a recently developed high-resolution regional 3D velocity model with accurate high-frequency waveform simulations. Located at the eastern margin of the Eurasian plate, the Korean Peninsula consists of complex geological units surrounded by thick sedimentary basins in oceanic areas. It exhibits large lateral variations in crustal thickness (> 10 km) and seismic velocity (>10% dlnVs) at its margins in the 3D model. Seismic waveforms were analyzed from regional earthquakes with local magnitudes > 3.4 that occurred within and around the peninsula recorded by local broadband arrays. Moment tensor components were inverted together with event locations using the numerically calculated Fréchet derivatives of each parameter at periods ≥ 6 s. The newly determined solutions were compared with the results calculated from the one-dimensional (1D) regional velocity model, revealing a significant increase in a double-couple component of > 20% for earthquakes off of the coastal margins. Further, compared to initial solutions, ≤ 5 km change in depth was observed for earthquakes near the continental margin and sedimentary basins. The combination of a detailed 3D crustal model and accurate waveform simulations led to an improved fit between data and synthetic seismograms. Accordingly, the present results provide the first confirmation of the effectiveness of using 3D velocity structures for accurately constraining earthquake source parameters and the resulting seismic wave propagation in this region. We suggest that accurate 3D wave simulations, together with improved source mechanisms, can contribute a reliable assessment of seismic hazards in regions with complex continental margin structures and sedimentary basins from offshore earthquakes whose seismic waveforms can be largely affected by 3D velocity structures.